The Empowerment of The Council of Advisory and Preservation of Marriage (BP4) in Shaping Sakinah Families - Samsul Samsul; Mohd. Fauzi Abu Husen (Justicia Islamica, 2020)
Divorce cases in the Religious Courts of Lampung Province increase every year, which shows that the performance of BP4 Lampung has not been optimal. Therefore, it needs to be evaluated scientifically. This study aims to find a form of reconstruction of the work management of BP4 Lampung in building a sakinah family. This study used qualitative research with a descriptive-analytical type. The approach used interviews, documentation, and observation. The work management of the BP4 Lampung in realizing the sakinah family includes: first, the selection of management and organizational members who have spiritual, cultural, and intellectual dimensions; second, giving the honorarium and the social guarantee; third, training and development. Reconstruction that can be carried out is budgeting, where after the issuance of the Law on regional autonomy, then BP4 Lampung, which is a partner of the Ministry of Religion Affairs and related agencies in improving the quality of marriage by developing the sakinah family movement, should get more attention in the whole budgeting problem by the government so that this program can be run optimally. To policymakers in Indonesia, both from the legislative and executive elements, along with the scholars, they should be proactive in paying attention to and following up on very complex Muslim problems, especially in the realm of Islamic family law and at the same time damaging the morals and values of the society in general. In this case, the most critical problem is the prevalence of divorce practices in Lampung, which hurt families' psychological development.